Demystifying Intercultural Service Encounters: Toward a Comprehensive Conceptual Framework - Sharma, Piyush; Tam, J.L.; Kim, N. (Sage Publications, 2009)
Customers and employees from different cultures are increasingly interacting with each other. However, there is little research in this area and it focuses mostly on the customers’ perspective. This article presents a conceptual framework for intercultural service encounters applicable to both customers and employees. Findings from an exploratory qualitative study show that perceived cultural distance and intercultural competence influence inter-role congruence, interaction comfort,adequate and perceived service levels, and satisfaction. These findings have important managerial implications for managing the expectations and perceptions of customers and employees involved in the intercultural service encounters and improving their satisfaction with the service experience.